The Effect of Additioning Microencapsulation Products of Noni Fruit Extract (Morinda citrifolia Linn) in The Ration on The Performance of Developer Phase Sentul Chickens - TANJUNG, FAISAL; Widyastuti, Tuti; Tanwiriah, Wiwin (Jurnal Ilmu Ternak Universitas Padjadjaran, 2024)
This study aims to determine the effect of adding microencapsulated noni fruit extract (MEBM) to the feed on the feed consumption, body weight gain, feed conversion, and sexual maturity age of Sentul phase developer chickens. The research was conducted from July to September 2023 at the Test Farm of the Faculty of Animal Husbandry Padjadjaran University. The research method used a Completely Randomized Design (CRD). There were five types of treatments, namely, P0 = basal ration without the addition of MEBM, P1 = basal ration + 50 mg/kg zinc bacitracin, P2 = basal ration + 75 mg/kg MEBM, P3 = basal ration + 150 mg/kg MEBM, P4 = basal ration + 225 mg/kg MEBM, and repeated four times. The measured variables were feed consumption, body weight gain, feed conversion, and sexual maturity age of Sentul phase developer chickens. The data were analyzed using analysis of variance and the differences in effects were tested using the Honestly Significant Difference (HSD) test with P0 as the negative control and P1 as the positive control. The results of the study showed that the addition of microencapsulated noni fruit extract (MEBM) at levels of 225 mg to the ration providing the best result on body weight gain and feed conversion, but it does not have a significant effect on feed consumption and sexual maturity age of Sentul phase developer chickens. It can be inferred that the addition of MEBM up to 225 mg/kg in the ration can replace the role of AGP zinc bacitracin as an antibiotic.